Fibronectin-, vitronectin- and laminin-binding proteins at the cell walls of Candida parapsilosis and Candida tropicalis pathogenic yeasts - Kozik, Andrzej (BMC Microbiol, 2015)
BACKGROUND: Candida parapsilosis and C. tropicalis increasingly compete with C. albicans—the most common fungal pathogen in humans—as causative agents of severe candidiasis in immunocompromised patients. In contrast to C. albicans, the pathogenic mechanisms of these two non-albicans Candida species are poorly understood. Adhesion of Candida yeast to host cells and the extracellular matrix is critical for fungal invasion of hosts. METHODS: The fungal proteins involved in interactions with extracellular matrix proteins were isolated from mixtures of β-1,3-glucanase– or β-1,6-glucanase–extractable cell wall-associated proteins by use of affinity chromatography and chemical cross-linking methods, and were further identified by liquid chromatography-coupled tandem mass spectrometry. RESULTS: In the present study, we characterized the binding of three major extracellular matrix proteins—fibronectin, vitronectin and laminin—to C. parapsilosis and C. tropicalis pseudohyphae. The major individual compounds of the fungal cell wall that bound fibronectin, vitronectin and laminin were found to comprise two groups: (1) true cell wall components similar to C. albicans adhesins from the Als, Hwp and Iff/Hyr families; and (2) atypical (cytoplasm-derived) surface-exposed proteins, including malate synthase, glucose-6-phosphate isomerase, 6-phosphogluconate dehydrogenase, enolase, fructose-1,6-bisphosphatase, transketolase, transaldolase and elongation factor 2. DISCUSSION: The adhesive abilities of two investigated non-albicans Candida species toward extracellular matrix proteins were comparable to those of C. albicans suggesting an important role of this particular virulence attribute in the pathogenesis of infections caused by C. tropicalis and C. parapsilosis. CONCLUSIONS: Our results reveal new insight into host–pathogen interactions during infections by two important, recently emerging, fungal pathogens.